Regeneration of Calcium Oxide (CaO) from Waste Gypsum via Two-step Reaction - Neshabran, Ramachandran; Gaanty Pragas, Maniam (2014)
The regeneration of calcium oxide from gypsum is the interest of this research. Gypsum was converted to calcium oxide via a two-step process involving chemical and thermal reactions. X-ray diffraction (XRD) was used to analyse the samples to identify the samples. Laboratory grade gypsum (LG) and waste gypsum (WG) were used in this research and successful conversion was done. Gypsum was converted into calcium hydroxide by reacting with sodium hydroxide, 0.1 M, solution. Then, calcium hydroxide was calcined, at 700°C, to form calcium oxide. The chemical changes were analysed using X-ray diffraction, wavelength dispersive X-ray fluorescence and thermogravimetric analysis methods.